Beyond Water Oxidation: Hybrid, Molecular-Based Photoanodes for the Production of Value-Added Organics - Natali, Mirco; Sartorel, Andrea; Ruggi, Albert (Frontiers in Chemistry, 2022)
The political and environmental problems related to the massive use of fossil fuels prompted researchers to develop alternative strategies to obtain green and renewable fuels, like hydrogen. The light-driven water splitting process (i.e., the photochemical decomposition of water into hydrogen and oxygen) is one of the most investigated strategies to achieve this goal. However, the water oxidation reaction still constitutes a formidable challenge due to its kinetic and thermodynamic requirements. Recent research efforts have been focused on the exploration of alternative and more favourable oxidation processes, such as the oxidation of organic substrates, to obtain value-added products besides solar fuels. In this mini-review some of the most intriguing and recent results are presented. In particular, attention is directed on hybrid photoanodes composed of molecular light absorbing moieties (sensitizers) and catalysts grafted onto either mesoporous semiconductors or conductors. Such systems have been exploited so far for the photoelectrochemical oxidation of alcohols to aldehydes in the presence of suitable co-catalysts. Challenges and future perspectives are also briefly discussed, with special focus onto the application of such hybrid molecular-based systems to more challenging reactions, such as activation of C-H bonds.